The Association of Serum Thrombomodulin with Endothelial Injuring Factors in Abdominal Aortic Aneurysm. (3rd April 2017) - Budzyń, Magdalena; Gryszczyńska, Bogna; Majewski, Wacław; Krasiński, Zbigniew; Kasprzak, Magdalena Paulina; Formanowicz, Dorota; Strzyżewski, Krzysztof Wojciech; Iskra, Maria
Abstract : Background. The aim of the present study was to evaluate the concentration of serum thrombomodulin (sTM) in the AAA patients and to examine its correlation with various factors which may potentially participate in the endothelial injury. Materials and Methods. Forty-one patients with AAA were involved and divided into subgroups based on different criteria. Concentration of sTM was measured using enzyme-linked-immunosorbent assay (ELISA). The results were compared with those obtained in 30 healthy age- and sex-matched volunteers. Results. The higher concentration of sTM was observed in AAA patients compared with those in controls volunteers [2.37 (1.97–2.82) ng/mL versus 3.93 (2.43–9.20) ng/mL, P < 0.001]. An elevated sTM associated significantly with increased triglycerides (TAG) [ P = 0.022], cholesterol [ P = 0.029], hsCRP [ P = 0.031], and advanced glycation end products (AGEs) [ P = 0.033]. Conclusions. The elevation of serum sTM level suggests that endothelial damage occurs in AAA pathogenesis. The correlations observed indicate that lipids abnormalities, inflammation, and oxidative stress may be involved in this destructive process.